2007 IEEE Nuclear Science Symposium Conference Record 2007
DOI: 10.1109/nssmic.2007.4436965
|View full text |Cite
|
Sign up to set email alerts
|

Improved image reconstruction in small animal PET using a priori estimates of single-pixel events

Abstract: Most small animal PET scanners are based on arrays of pixelated scintillators crystals. As the read-out of individual pixels would be too expensive, identification of the crystal of interaction is usually made by center of energy methods based for instance on Anger logic. This allows for a reduction in the number of signals to be acquired, but prevents the identification of multi-hit events, that is, events in that one (or several) photon produces several hits in the detector, thus blurring the correct positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Changes induced by therapy in SUV(tumor)/SUV(testicle) values appear 10% larger, in the average of the three rats, for improved OSEM with respect to standard OSEM. This is in accordance with previous studies on phantoms that also showed increased contrast and larger recovery coefficients for the improved 3DOSEM reconstruction [13].…”
Section: B Suvs Computationsupporting
confidence: 93%
See 2 more Smart Citations
“…Changes induced by therapy in SUV(tumor)/SUV(testicle) values appear 10% larger, in the average of the three rats, for improved OSEM with respect to standard OSEM. This is in accordance with previous studies on phantoms that also showed increased contrast and larger recovery coefficients for the improved 3DOSEM reconstruction [13].…”
Section: B Suvs Computationsupporting
confidence: 93%
“…In one of them, there is no attempt to correct for random counts, scatter or pile-up in the acquisition data. In the other one (improved 3D-OSEM), corrections for randoms, scatter and pile-up are incorporated in the reconstruction algorithm [13].…”
Section: B Calibration Acquisitions and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We selected this study for quantification because the expected ideal profile is well known and the heart has also been used for similar comparisons elsewhere. 18,17,19 All the results presented are expressed as a percentage with respect to a baseline reconstruction consisting of FBP with a ramp filter only. Table I shows the filters used in the comparison.…”
Section: Iid Assessment Of Resultsmentioning
confidence: 99%
“…Indeed, with the help of detailed simulations, it is possible to establish a correlation between the parameters recorded by the scanner for each count, such as rate of coincidences and, if available, of singles too, XY-positioning of the interaction as provided by standard Anger algorithms, energy deposited in the detectors and the likelihood of the count acquired of being assigned to the correct crystal of first interaction. Details of this procedure have been given in España et al (2007b). Due to detector pile-up, coincidences acquired at high rates will suffer, more often than the ones at low rates, of wrong crystal positioning.…”
Section: Advanced Use Of Simulationsmentioning
confidence: 99%